The Sikep Resistance as an Anti-Colonial Movement - Firza Azzam Fadilla; Daya Negri Wijaya; Muhammad 'Afwan Mufti (Universitas Hamzanwadi, 2026)
In the late 19th century, various social resistance movements emerged among Javanese farmers one of these was the Sedulur Sikep, or Saminis movement, meanwhile the Dutch East Indies government carried out a propaganda campaign through colonial newspapers to create a negative stigma against these rebel groups. The objective of this study is to examine and analyze the paradigm and negative stigma toward the Samin movement established by the Dutch East Indies Government, which has persisted into the contemporary era, through the lens of Pierre Bourdieu’s theory of symbolic power. This study employs a historical method, utilizing primary sources from the Dutch East Indies period to examine the origins of this negative paradigm. The theory of symbolic power is applied to analyze how colonial discourse shaped public perception and marginalized the Samin Movement. Findings indicate that the colonial government employed symbolic power through mass media propaganda, instilling what can be understood as “mind control” to influence public attitudes by disseminating narratives that delegitimized the movement. This study highlights that the Saminis movement is an important example of nonviolent resistance, critical social consciousness, and a strong cultural identity. These historical values remain relevant in a contemporary context, particularly in addressing the stigma still attached to the Sedulur Sikep community. Therefore, this history can be integrated into culturally-based local history education to foster historical awareness, strengthen identity formation, and promote the development of inclusive and critical character among future generations.